Management of Female and Functional Urology Patients During the COVID Pandemic - TARCAN, TUFAN (ELSEVIER, 2020)
Context: Coronavirus disease 19 (COVID-19) has changed standard urology practice around the world. The situation is affecting not only uro-oncological patients but also patients with benign and disabling conditions who are suffering delays in medical attention that impact their quality of life. Objective: To propose, based on expert advice and current evidence where available, a strategy to reorganize female and functional urological (FFU) activity (diagnosis and treatment). Evidence acquisition: The present document is based on a narrative review of the limited data available in the urological literature on SARS-Cov-2 and the experience of FFU experts from several countries around the world. Evidence synthesis: In all the treatment schemes proposed in the literature on the COVID-19 pandemic, FFU surgery is not adequately covered and usually grouped into the category that is not urgent or can be delayed, but in a sustained pandemic scenario there are cases that cannot be delayed that should be considered for surgery as a priority. The aim of this document is to provide a detailed management plan for noninvasive and invasive FFU consultations, investigations, and operations. A classification of FFU surgical activity by indication and urgency is proposed, as well as recommendations adopted from the literature for good surgical practice and by surgical approach in FFU in the COVID-19 era. Conclusions: Functional, benign, and pelvic floor conditions have often been considered suitable for delay in challenging times. The long-term implications of this reduction in functional urology clinical activity are currently unknown. This document will help functional urology departments to reorganize their activity to best serve their patients. Patient summary: Many patients will suffer delays in urology treatment because of COVID-19, with consequent impairment of their physical and psychological health and deterioration of their quality of life. Efforts should be made to minimize the burden for this patient group, without endangering patients and health care workers. (C) 2020 European Association of Urology. Published by Elsevier B.V. All rights reserved.
Keywords: COVID-19; Female urology; Functional urology; Neurourology; Prioritization; Telehealth; HARMFUL